2022
DOI: 10.1007/s11482-022-10109-0
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Economics, Public Policy and Mental Health

Abstract: General public’s mental health can be affected by the public policy response to a pandemic threat. Britain, Italy and Sweden have had very distinct approaches to the COVID-19 pandemic: early lock-down, delayed lock-down and no-lock-down. We develop a novel narrative economics of language Culture-Based Development approach, and using Google trend data for seed keywords, death and suicide, we reach two main conclusions: (i) while countries had a pre-existing culturally relative disposition towards death-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Nevertheless, during a crisis, such as the COVID-19 pandemic, it is common for everyone to experience increased levels of distress and anxiety, particularly the sentiment of social isolation (American Medical Association, 2020). A growing number of studies document worsening mental health status and levels of well-being (Adams-Prassl et al 2020b;Brodeur, Clark, Fleche, & Powdthavee, 2021;Davillas & Jones, 2020;de Pedraza et al, 2020, andTubadji et al, 2020).…”
Section: Health Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, during a crisis, such as the COVID-19 pandemic, it is common for everyone to experience increased levels of distress and anxiety, particularly the sentiment of social isolation (American Medical Association, 2020). A growing number of studies document worsening mental health status and levels of well-being (Adams-Prassl et al 2020b;Brodeur, Clark, Fleche, & Powdthavee, 2021;Davillas & Jones, 2020;de Pedraza et al, 2020, andTubadji et al, 2020).…”
Section: Health Outcomesmentioning
confidence: 99%
“…In the opposite case, using an experimental set-up, Bogliacino et al (2020) find that a negative shock triggered by COVID-19 lowers cognitive functionality and increases risk aversion and the propensity to punish others, that is negative reciprocity. Public mental health is also affected by the cognitive bias related to the diffusion of public death toll statistics (Tubadji et al, 2020). These needs are all the less likely to be addressed given the lower levels of provision of health care and social work services.…”
Section: Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, at the same time, Luchetti and others (2020) found no effect of COVID‐19 on the happiness trajectories of individuals. Tubadji and others (2020) reported that Google searches for suicide decreased during the pandemic. And while Groarke and others (2021) report sleep effects that may relate to unhappiness, the work of Berniell and others (2021) found that usually isolated (i.e., relatively deprived in socializing) elderly individuals actually felt better off in terms of their life satisfaction during the COVID‐19 lockdowns, potentially because the lockdown imposed on all essentially reduced their feelings of relative social deprivation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of the highly transmissible nature of the virus, governments were forced to adopt restrictive policies to protect their citizens, such as city lockdowns, mandatory masks, and mandatory vaccinations. The COVID-19 outbreak and restrictive government policies may cause widespread psychological harm [2,3]. According to Lancet, the COVID-19 pandemic has caused an additional 53.2 million cases of major depressive disorder worldwide (growth of 27.6%) [4].…”
Section: Introductionmentioning
confidence: 99%